Penggunaan Tepung Daun Kelor pada Pembuatan Crackers Sumber Kalsium - Yustika Fahreina Mazidah; Indah Kusumaningrum; Debby Endayani Safitri (ARGIPA (Arsip Gizi dan Pangan), 2018)
Moringa oleifera is one of the green vegetables rich in nutrients and began to be developed in processed food products. The purpose of this study was utilize Moringa oleifera leaves as processed foods that can be consumed as snack by teenagers, helping to fulfill their nutritional needs. This study used a randomized experimental design one factorial with two repetitions. The substitution level of Moringa Leaf flour in the making of crackers were F0 (100:0), F1 (90:10), F2 (85:15), and F3(80:20). The best Moringa leaf crackers was determined by hedonic test with semi-trained panelists. Analysis of data used Kruskall Wallis test, followed by Mann Whitney test. It was known that the higher level of Moringa leaves flour substitution the lower level of panelists’s acceptance (color, texture, flavor, and aroma). The selected product was F1, had a brownish-green color, crispy texture, unbitter taste, and normal aroma. This cracker, per 100 g, contained energy 456.1 kcal, 67.1 g of carbohydrates, 8.9 g proteins, 16.9 g fats, 3.05 mg irons, and 324 mg calcium. The selected crackers can be claimed as snack of calcium source. Keywords: Moringa Oleifera, Moringa Leaf Flour, Moringa Leaves Crackers, Calcium, Iron.